Forage mass, botanical composition and stocking density of bermudagrass overseeded with forage legumes - Nunes Assis dos Anjos, Amanda; Olivo, Clair Jorge; Pereira Leme, Denise; Flôres Aguirre, Priscila; de Almeida Pires, Franciane; Ribeiro Falk, Débora (Revista Ceres, 2017)
Pastures of the genus Cynodon are being cultivated alone in conventional production with high rates of nitrogen fertilizer. Information and research about its use on mixed-pasture system is scarce. The objective of this study was to evaluate three grazing systems with coastcross-1 (CC) + 100 kg N ha-1 year-1 + common vetch; CC + 100 kg N ha-1 year-1 + arrowleaf clover; and CC + 200 kg N ha-1 year-1. The experiment was carried out from May 2013 to April 2014. The sward height, forage mass, botanical composition, leaf:stem ratio, and animal stocking density were evaluated. Experimental design was completely randomized with three treatments (grazing systems) and three replicates (paddocks) in completely split-plot time (grazing cycles). The average stocking rate was 7.0, 6.8, 6.8 cows ha-1 day-1 for the respective forage systems. Better results were found with coastcross-1 mixed with common vetch + 100 kg N ha-1 year-1 in winter and spring and coastcross-1 alone + 200 kg N ha-1 year-1 in autumn.